Assessing adaptive capacity of climate-vulnerable farming communities in flood-prone areas: insights from a household survey in South Punjab, Pakistan - Aqib, S.; Seraj, M.; Ozdeser, H.; Khalid, Sidra; Raza, M. H.; Ahmad, T. (Elsevier, 2024)
Climate change poses a significant threat to agricultural systems worldwide. In Pakistan, an agrarian country where the majority of the population relies on agriculture for their livelihoods, the impacts of climate change can be particularly devastating. Understanding the adaptive capacity of farmers is crucial in order to identify effective strategies for coping with the impacts of climate change. This study aimed to assess the adaptive capacity of farmers in Rajanpur and Dera Ghazi Khan, two flood-prone districts of South Punjab, Pakistan. Data were collected in October 2022 from 448 farmers through multistage stratified random sampling, and multivariate regression and bivariate probit models were used to analyze the likelihood of farmers adopting certain joint strategies and the impact of socioeconomic factors on their decision-making. Results indicated that concern for climate change and knowledge of market value of crops were significant determinants for farmers adopting joint strategies, while farmers with more experience and alternate sources of income were less likely to do so. Increased irrigation was a top strategy used despite its potential negative environmental impacts. Findings highlight the need for a holistic approach to climate adaptation that considers complex social, economic, and environmental factors and appreciates the complex decision-making process that farmers undergo. Understanding the local context is key to developing effective interventions to support climate resilience and sustainable livelihoods in agricultural communities.